Analysis of Knowledge Management, Work Innovation on Achievements and Progress of Gorontalo Province’s Government Organizations - Mendo, Andi Yusniar (AIBPM Publisher, 2019)
The research aims:1) analyzed the effect of knowledge management, job innovation and prestation have positive and significant toward progress of organization; 2) analyzed the effect of knowledge management and job innovation have positive and significant toward prestation; and 3) analyzed the effect of knowledge management have postive and significant toward job innovation. The location of research in Gorontalo Province, in Government of Gorontalo Province. Population of research all of civil servant in Government of Gorontalo Province as amount 3.086 persons. And sample in Slovin formulation 10% obtained 97 respondents. Data from questioner to analyzed with path analysis. The result of research to found: 1) the knowledge management have positive and significant toward progress of organization. The applied of knowledge management to actualize and get significant contribution toward the progress of organization; 2) job innovation possitive and significant toward progress of organization. The innovation have suitable with the need of job to incerased the progress of organization; 3) prestation have positive and significant toward progress of organization. The prestation which achieve to support in progress of organization; 4) knowledge management positive and significant toward prestation. The knowledge management able to result of employee which have prestation in job field; 5) job innovation positive and significant toward prestation. Innovation in continueing to oriented on achieve of prestation; 6) the knowledge management have positive and significant toward innovation. The knowlegde management suitable with job innovation. Keywords: Knowledge Management, Job Innovation, Prestation and Progress of Organization